FROM HERETICAL FATWA TO JUDICIAL REVIEW: SALAFI, ULAMA, AND COMMUNAL CONFLICT IN ACEH - Alhusni; Mustajab, Muhammad; Kurniawan, Edi (Balai Penelitian dan Pengembangan Agama Jakarta, 2024)
The Salafi preaching style in Aceh has prompted a response from the Aceh Ulema Consultative Council (MPU/Majelis Permusyawaratan Ulama) through a heretical fatwa on several Salafi teachings leading to communal conflict in Aceh. This article analyzes the socio-political background of the fatwa’s emergence, its impact on socio-religious conflict in Aceh, and Salafists’ resistance through a judicial review of the MPU’s legality. Combining literature and field studies, this paper demonstrates that the socio-religious conflict between Salafists and Acehnese society stems from the former’s truth claims regarding khilāfiyya issues. This is evident in the Salafi preaching style, which criticizes and hereticates some traditional Acehnese Muslim practices, that generated antagonistic responses from the MPU, society, and the Aceh government. The conflict has intensified after Salafists challenged the MPU’s legality in the Supreme Court of Indonesia despite its decline, which further solidified opposition to Salafi teachings and led to their marginalization in Aceh. This paper recommends that promoting tolerance by both parties is essential to resolving the conflict.